Foreign Direct Investment, Economic Growth, and Governance in China: An Empirical Study - Jiaying, Li; Ridzuan, Abdul Rahim; Bose, Jacob; Mukthar, K. P. Jaheer; Thomas, Anish; Abd Samad, Khairunnisa; Abd Rahman, Nur Hayati; Thomas, Sajan N. (International Journal of Economics and Financial Issues, 2025)
In this study, the direct and indirect effect of FDI on governance was analyzed using the ARDL model with data spanning from 1990 to 2023. The analysis looked at FDI interaction with economic growth and financial openness. An analytical framework was constructed, including macroeconomic factors like trade openness, real GDP per capita, and financial development. Based on the analysis, governance can be impacted by FDI in a complex and non-linear manner. In the short-run perspective, the degree of impact of FDO on governance seemed to be mixed. However, in the long-run view, the impact leaned more positively, although not always statistically significant. Governance benefits from economic growth and vice versa. Thus, these two factors have a mutual positive relationship. However, trade openness seemed to hinder governance growth, marked by institutional pressures and regulatory challenges of deeper integration into global markets. Financial development, while theoretically expected to improve governance through greater transparency and market discipline, does not show significant long-term effects, suggesting that financial governance reform in China remains incomplete. The findings highlight the importance of optimising the quality of FDI, strengthening institutional capacity, and combining economic openness with governance reforms. This study not only contributes to the academic literature on FDI and governance but also provides practical policy implications for China to continue to attract high-quality FDI, improve its governance capacity, and achieve high-quality development in the context of globalisation and sustainable development.